Molecular phylogeny of selected species of the family Tetrigidae (Orthoptera) in Mindanao, Philippines - Mondia, Evelyn Bogo (CMU Graduate Journal, 2017)
The morphological characteristics revealed 49 morphs-species of tetrigids distinguished by the length of their legs, eyes and pronotum. There were strong similarities observed between IMPA8 and KAL10, KAL10 and KAL11, KAL10 and KIA1, APO2 and KIA2, IMPA2 and KIA3, APO1 and KIA5, APO3 and KIA6, APO4 and KIA7 and APO2 and APO4. DNA extraction was done using the Promega Wizard® Genomic DNA Purification Kit. Gene sequences were obtained by polymerase chain reaction (PCR) amplification with the use of primers LCO 1490 5' - GGT CAA CAAATC ATA AAG ATA TTG G - 3' and HCO 2198 5' - TAA ACT TCA GGG TGA CCA AAA AAT CA 3'. A genomic sequence of 645 base pairs was obtained from the 8 tetrigid samples. BLAST analysis was able to identify Tetrixto the genus level. The rest of the species do not have records yet and were barcoded for the first time. The phylogeny of the tetrigids was analyzed based on mitochondrial cytochrome oxidase 1 (CO1) sequences isolated from selected species in Mindanao. The phylogenetic signals in the CO1 were examined under analytical regimens of maximum likelihood (ML) and Bayesin inference (BI) with the highest bootstrap values. The CO1 sequence is useful in identifying the tetrigids to the genus level. Tetrigids formed a monophyletic group based on the clade.